2019
DOI: 10.18699/vj19.459
|View full text |Cite
|
Sign up to set email alerts
|

Progress in plant genome sequencing: research directions

Abstract: Геномные технологии претерпели значительные изменения с момента публикации первой последовательности генома растения Arabidopsis thaliana. Исследователи приняли на вооружение новые алгоритмы и технологии секвенирования и биоинформационные подходы для получения геномной последовательности, транскриптома и экзома для модельных и культурных видов растений, что позволило сделать глубокие выводы о биологии растений. В результате снижения затрат на секвенирование благодаря улучшению методов сборки и анализа геномов,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…The genome sequence is the basis for a chromosome structure studying, a distribution of repetitive and coding sequences, and genes identification and annotation (Bragina et al, 2019). The different species genomes information allows a comparative phylogenetic analysis to study relationships among species, their origins, and evolutionary features (Marchant et al, 2016;Wendel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genome sequence is the basis for a chromosome structure studying, a distribution of repetitive and coding sequences, and genes identification and annotation (Bragina et al, 2019). The different species genomes information allows a comparative phylogenetic analysis to study relationships among species, their origins, and evolutionary features (Marchant et al, 2016;Wendel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A single organism chromosome sequences serve as the basis ("reference" genome) for studying other genomes of the same species. The number of sequenced, assembled and annotated plant reference genomes increases every year (Bragina et al, 2019). The Ensembl Plants database version 48 (September 2020) contains 93 assembled and annotated plant genomes (Howe et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, the efficiency of target enrichment has been proven for the study of the nucleotide diversity of polyploid species with a large, repetitive and heterozygous genome (Bragina et al, 2019). This method has been used in various crops, including in the study of ecological adaptation in barley (Russell et al, 2016), the identification of wheat disease resistance genes (Steuernagel et al, 2016), the cataloging of mutations in rice (Henry et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Bragina et al (2019) [3] concluded in his experiment that the cost of sequencing is continuously falling, thanks to continual advancements in DNA sequencing technologies. Plant genome sequencing is becoming increasingly commonplace and more efficient.…”
Section: Key Role Of Advancing Genomics Toolsmentioning
confidence: 99%